Superimposed squeeze and rotational flows of Newtonian and power-law fluids - Rubio-Hernández, Francisco José; Velázquez-Navarro, José Francisco; Rodríguez Lara, Miriam (AIP Publishing, 2024)
This study theoretically predicted the response of superimposed squeeze and rotational flows (SSRF) of fluids with different viscous behaviors (i.e., Newtonian, shear-thinning, and shear-thickening fluids). The theoretical predictions were verified using the plate-plate geometry for the SSRF measurements with the Newtonian and power-law fluids. In all the cases, the squeeze force increased as the gap decreased, but the response was very different for each rheological behavior. The variation in the squeeze force with the gap was not affected by the superimposed rotational shear stress value, owing to the nondependency of the viscosity on the shear for Newtonian fluids. However, for the power-law fluids, the squeeze force variation with the gap value was based on the value of the superimposed shear stress value. The decrease and increase in the viscosity with the shear stress for the shear-thinning and shear-thickening fluids, respectively, resulted in opposite trends of the squeeze force with the gap value variation. For the shear-thinning fluids, the squeeze force for each gap value decreased with increasing superimposed rotational shear stress. The opposite trend was observed for the shear-thickening fluid. In the absence of wall slip, the theoretical predictions well agreed with the experimental results.
Keywords: Física; Dinámica de fluidos; Non Newtonian fluids; Rheometer; Rheological properties; Shear thickening; Shear thinning